Histological Effects of Creatine Monohydrate Supplementation on Muscle Tissue in Wistar Rats - Isabela Ferreira Silveira ARRUDA; Amilton IATECOLA; Vanessa Zanoni CARVALHAES; Marcelo Rodrigues da CUNHA; Victor Augusto Ramos FERNANDES (Modern Medicine)
Creatine is a dietary supplement with the potential to stimulate the phosphocreatine pathway and protein synthesis, through the stimulation of PI3eK/AKT and mTOR responsible for the proliferation and differentiation of satellite cells, responsible for hypertrophy. The present study aimed to evaluate the morphological effects of the use of creatine monohydrate on the soleus muscle tissue of 26-month-old Wistar rats. Methods: Twelve Wistar rats were divided into two groups of six animals each. Group 1 was not supplemented with creatine and received a standard diet consisting of water and food. Group 2 received the same diet, but was supplemented with creatine monohydrate at a dose of 0.03 mg/kg of body weight diluted in 200 ml of drinking water for 8 weeks. Results: The supplementation promoted morphological and morphometric effects on the soleus muscle tissue, promoting changes in the perimeter and area of the muscles of the animals treated with the supplement. It is estimated that this supplement may promote, in addition to increasing the cross-sectional area of myocytes, increased stimulation of the protein synthesis pathway associated with PI3K/AKT.